MINAT BACA PUSTAKAWAN PDII-LIPI: SEBUAH KAJIAN DESKRIPTIF - Nani Rahayu, Rochani; Tupan, Tupan; Nashihuddin, Wahid (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2012)
The general objective of this research is to determine the CSDI – IIS (Centre of Scientific Documentation and Information – Indonesian Institutes of Sciences) librarians’ reading interest. While the specific objectives are to determine : 1) the types and subject of reading materials which are interesting for librarians, 2) the reading time of librarians, 3) the amount of literature read by librarians every day; 4) the preferred reading materials by librarians; 5) the factors and purposes of reading activity, and 6) the place of librarians frequently used for reading. The research question is: How is the condition of reading interest of CSDI-IIS librarians regarding with the types and subject of reading materials, the reading time, the reading amount, the reading language, the reading preferences, the factors and purposes of reading motivation, and the places to read used by librarians. This type of research is descriptive, by using observation method and questionnaires distributed to librarians of the CSDI-IIS. Number of questionnaires distributed are 60 questionnaires, but only 41 librarians (68.33%) who filled out the questionairres. The data obtained are processed and analyzed using descriptive method for analyzing and explaining the actual condition of the object. The expected result is the increasing of reading interest of CSDI-IIS librarian.